The adventure zone. Here there be gerblins - McElroy, Clint, 1955-; McElroy, Griffin; McElroy, Travis, 1983-; McElroy, Justin, 1980-; Pietsch, Carey (2018)
"Join Taako the elf wizard, Merle the dwarf cleric, and Magnus the human warrior for an adventure they are poorly equipped to handle AT BEST, guided ("guided") by their snarky DM, in a graphic novel that, like the smash-hit podcast it's based on, will tickle your funny bone, tug your heartstrings, and probably pants you if you give it half a chance." --
Keywords: Quests (Expeditions) -- Comic books, strips, etc; Magic -- Comic books, strips, etc; Fantasy comics; Humorous comics; Graphic novels; Comics (Graphic works); Comics (Graphic works); Graphic novels